Gastrointestinal Symptoms in Women With Endometriosis and Microscopic Colitis in Comparison to Irritable Bowel Syndrome: A Cross-Sectional Study - Ek, Malin; Roth, Bodil; Bengtsson, Mariette; Ohlsson, Bodil (Turkish Journal of Gastroenterology, 2021)
Background: Gastrointestinal (GI) symptoms similar to irritable bowel syndrome (IBS) are often present in women with endometriosisand microscopic colitis (MC). The objective of this study was to estimate GI symptoms in IBS, endometriosis, and MC, to compare theclinical expression of the diseases.Methods: Women with IBS, endometriosis, and MC were identified by diagnosis codes at a tertiary center. The patients had to completethe visual analog scale for IBS to estimate specific GI symptoms. Women fulfilling Rome III criteria for IBS were diagnosed as IBS(n = 109) and divided into subgroups depending on predominating symptoms. Women diagnosed with endometriosis (n = 158) and MC(n = 88) were evaluated whether they also fulfilled the Rome III criteria for IBS.Results: Women with IBS experienced aggravated abdominal pain, diarrhea, bloating and flatulence, nausea and vomiting, the urgencyto defecate, the sensation of incomplete evacuation and intestinal symptom’s influence on daily life, and impaired psychological wellbeing,compared to women with endometriosis. When patients with endometriosis also fulfilled the criteria for IBS, all symptoms in the2 cohorts, except intestinal symptom’s influence on daily life, were equal. Women with IBS or diarrhea-predominated IBS experiencedaggravated abdominal pain, bloating and flatulence, intestinal symptom’s influence on daily life, and impaired psychological well-beingcompared to MC, but at equal levels as MC with IBS-like symptoms.Conclusions: Women with IBS generally experience aggravated GI symptoms and impaired psychological well-being compared to endometriosisand MC. Patients with endometriosis or MC, in combination with IBS, express similar symptoms as patients with sole IBS.